Comparison of striatal dopamine transporter levels in chronic heroin‐dependent and methamphetamine‐dependent subjects. (4th June 2015) - Yuan, Jie; Liu, Xing Dang; Han, Mei; Lv, Rong Bin; Wang, Yuan Kai; Zhang, Guang Ming; Li, Yu
Abstract: To compare the effects of heroin and methamphetamine (METH) addiction on dopamine transporters (DATs) in the same dose and duration, we assessed DAT levels in the striatum by 99m Tc‐TRODAT‐1 single‐photon emission computed tomography (SPECT) brain images in people with heroin and METH dependence. We recruited 21 healthy human controls, 23 heroin‐dependent subjects and 25 METH abusers. The heroin‐ and METH‐dependent subjects exhibited negative urine toxicology after undergoing physiological detoxification. All subjects underwent SPECT brain imaging, and specific tracer uptake ratios (SURs) were assessed bilaterally in the regions of interest. A significant SUR reduction in heroin‐dependent subjects and METH‐dependent subjects compared with healthy controls was found in the left striatum, right striatum, left caudate nucleus, right caudate nucleus, left putamen and right putamen. There were no significant differences in the heroin group and METH group for the left striatum, right striatum, left caudate nucleus, right caudate nucleus, left putamen and right putamen. The scores of craving, HAMA (Hamilton Anxiety Rating Scale), in heroin abusers were lower than in the METH abusers. Our results show that people with heroin and METH dependence who are currently abstinent had lower DAT levels in the striatum than healthy controls. There were no differences in striatal DAT in heroin and METH users. These results suggest that chronic heroin and METH abuse appears to produce similar effects in striatal DAT in humans. METH users may have more serious craving and anxiety symptoms than heroin users with prolonged abstinence.